Investigating students’ spatial ability in the context of cultural differences - Kanti Warih Ade Indriani; Baiq Rika Ayu Febrilia; Fauzi Galih Lutfianto (Universitas Islam Negeri (UIN) Mataram, 2020)
[English]: Culture is believed to be one of the factors that influence mathematical learning. It supports the idea of ​​culturally responsive mathematics education. This qualitative study aimed to investigate students’ spatial abilities and the possible linkages of cultural differences (parenting) with the abilities. Data were collected through questionnaires, initial ability tests, spatial ability tests, and interviews. The study began with the identification of the students’ culture from two different rural areas, namely Lalar Liang (LL) and Labu Lalar (LB), using a questionnaire, and a preliminary test was administered for the classification of students' mathematical abilities. Furthermore, six students were selected as subjects from the two cultures based on the high, medium, and low groups to be given a spatial reasoning test. In the last stage, the selected subjects were interviewed to identify the possible relationship between their culture and spatial ability. The students’ answers were analyzed according to the indicators of spatial ability and linked to the culture of students from the two areas. The findings show that students from LL have a better understanding of the dimensions of objects from various sides and the changes of the object shapes after rotating than from LB. The results of the interview indicated that there was a possible relation of parenting on students' thought patterns in solving mathematics problems. However, this needs to be proven by further empirical studies. Keywords: Spatial abilities, Cultural differences, Parenting, Mathematical learning [Bahasa]: Kultur dipercaya menjadi salah satu faktor yang mempengaruhi pembelajaran matematika. Hal tersebut mendukung berkembangnya ide pendidikan matematika responsif kultur. Penelitian kualitatif ini bertujuan menginvestigasi kemampuan spasial siswa dan kemungkinan keterkaitan perbedaan kultur (pola asuh) dengan kemampuan spasial siswa. Data penelitian diperoleh melalui angket, tes kemampuan awal, tes kemampuan spasial, dan wawancara. Penelitian dimulai dengan identifikasi kultur siswa yang berasal dari dua desa berbeda, yaitu desa Lalar Liang (LL) dan Labu Lalar (LB), melalui angket dan pemberian tes awal untuk klasifikasi kemampuan siswa. Selanjutnya, enam siswa dipilih sebagai subjek dari dua kultur berdasarkan kelompok tinggi, sedang dan rendah untuk diberikan tes penalaran spasial. Pada tahap terakhir, subyek terpilih diwawancarai untuk mengidentifikasi kemungkinan hubungan kultur dengan kemampuan spasial. Hasil tes siswa dianalisis sesuai dengan indikator kemampuan spasial dan dikaitkan dengan pola asuh siswa dari dua desa tersebut. Hasil penelitian menunjukkan bahwa siswa yang berasal dari desa LL lebih mampu memahami dimensi bangun dari berbagai sisi dan perubahan bentuk benda setelah dirotasi, dibandingkan pada siswa yang berasal dari LB. Hasil wawancara mengindikasikan adanya pengaruh pola asuh terhadap pola pikir siswa dalam menyelesaikan masalah matematika. Tetapi, hal ini perlu dibuktikan melalui kajian yang lebih mendalam secara empiris. Kata kunci: Kemampuan spasial, Perbedaan budaya, Pola asuh, Pembelajaran matematika